Psilocin poisoning and its derivatives - Majewska, Magdalena; Szponar, Jarosław; Karakuła, Hanna; Kołodziej, Małgorzata; Lewandowska-Stanek, Hanna (Current Problems of Psychiatry, 2012)
Hallucinogenic mushrooms containing psilocin action and psilocybin has been known for centuries. They belong to the genera: Conocybe, Psylocibe, Gymnophilus and Panaeolus. Psilocin name is derived from Greek and loosely translated means "naked (psilo) head (Cybe)". In many cultures of these fungi were abused during the ritual and mystical rites. Psilocin is used mainly in order to apply the so-called. Tripping, or hallucinogenic pleasurable sensations, mainly in the form of visual hallucinations. However, it can cause side effects in the form of: tachycardia, hypotension, organ damage, and even the occurrence of unwanted "bad Tripping" so-called. "Bad trips". In Poland, despite the ban on their cultivation and use are still popular stimulant mainly among young people. Recently, more popular and more available on the illicit market are their synthetic derivatives. These include, among others 4-Acetoxy-N, N-dimethyltryptamine, known as 4-AcO-DMT. The paper presents the main symptoms of intoxication use and psilocin and its derivatives, as well as the rules of conduct in acute poisonings. Furthermore, a case of a 16-year-old patient hospitalized at the Regional Center of Clinical Toxicology in Lublin due to substance intoxication psychostimulants 4-AcO-DMT.